2020
DOI: 10.1177/1753466620977376
|View full text |Cite
|
Sign up to set email alerts
|

Modified and simplified clinically important deterioration: multidimensional indices of short-term disease trajectory to predict future exacerbations in patients with chronic obstructive pulmonary disease

Abstract: Background and aims: Various prediction indices based on the single time point observation have been proposed in chronic obstructive pulmonary disease (COPD), but little was known about disease trajectory as a predictor of future exacerbations. Our study explored the association between disease trajectory and future exacerbations, and validated the predictive value of the modified and simplified short-term clinically important deterioration (CID). Methods: This study was a multicenter, prospective observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This phenomenon was also observed in patients with frequent and severe exacerbation. This is consistent with previous research showing that CID-C based on CAT deterioration was associated with the risk of future exacerbation [ 15 ]. This reflects that the occurrence of short-term CAT deterioration may be associated with future exacerbations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This phenomenon was also observed in patients with frequent and severe exacerbation. This is consistent with previous research showing that CID-C based on CAT deterioration was associated with the risk of future exacerbation [ 15 ]. This reflects that the occurrence of short-term CAT deterioration may be associated with future exacerbations.…”
Section: Discussionsupporting
confidence: 93%
“…Zhao et al. [ 15 ] found that the CID based on 2 points of CAT deterioration (CID-C) shows a good predictive value for the risk of exacerbation in the future. Therefore, short-term changes in CAT scores may be associated with the risk of exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…An exacerbation is a COPD progression that requires antibiotics, or oral corticosteroids, or hospitalization [ 4 ]. A current-smoker has had smoking exposure of ≥10 pack-years, while an ex-smoker has had ≥10 pack-years but has not smoked for more than 6 months [ 11 ]. The GOLD 2019 document defines grades 1–4 as follows: grade 1, FEV1 ≥ 80%pred; grade 2, FEV1 50–79%pred; grade 3, FEV1 30–49%pred; and grade 4, FEV1 < 30%pred [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…As for smoking history, we defined “Never-smoker” as smoking exposure less than 10 pack-years, “Ex-smoker” as not less than 10 pack-years but smoking cessation more than 6 months. 13 …”
Section: Methodsmentioning
confidence: 99%